An overview of functional and stereological evaluation of spermatogenesis and germ cell transplantation in fish - Nóbrega, R. H.; Batlouni, S. R. [UNESP]; França, L. R. (Springer Nature, 2009)
Although there are almost thirty-thousand species of fish living in a great variety of habitats and utilizing vast reproductive strategies, our knowledge of morphofunctional and quantitative aspects of testis structure and spermatogenesis is still incipient for this group of vertebrates. In this review, we discuss aspects that are important to better understanding of testis structure and function, and of the development of germ cells (GC) during spermatogenesis. To achieve this, we have recently completed a number of studies presenting morphometric and functional data related to the numbers of GC and Sertoli cells (SC) per each type of spermatogenic cyst, the number of spermatogonial generations, the SC efficiency, and the magnitude of GC loss that normally occurs during spermatogenesis. We also investigated SC proliferation and the relationship of this important event to early spermatogenic cysts. The available data strongly suggest that SC proliferation in sexually mature tilapia is the primary factor responsible for the increase in testis size and for determination of the magnitude of sperm production. The influence of temperature on the duration of spermatogenesis in tilapia was also evaluated and we have used this knowledge to deplete endogenous spermatogenesis in this teleost, in order to develop an experimental system for GC transplantation. This exciting technique results in new possibilities for investigation of spermatogenesis and spermatogonial stem cell biology, creating also an entirely new and promising scenario in biotechnology - transgenic animal production and the preservation of the genetic stocks of valuable animals or endangered species. © Springer Science+Business Media B.V. 2008.
Keywords: Germ cells transplantation; Sertoli cells; Spermatogenesis; Spermatogonial stem cells; Testis; animal; animal disease; fish; germ cell; histology; male; physiology; review; spermatogenesis; testis; transplantation; Animals; Fishes; Germ Cells; Male; Transplants; Animalia; Teleostei; Tilapia; Vertebrata